Does integrated academic and health education prevent substance use? Systematic review and meta‐analyses. (15th February 2018) - Melendez‐Torres, G. J.; Tancred, T.; Fletcher, A.; Thomas, J.; Campbell, R.; Bonell, C.
Abstract: Background: Prevention of substance (alcohol, tobacco, illegal/legal drug) use in adolescents is a public health priority. As the scope for school‐based health education is constrained in school timetables, interventions integrating academic and health education have gained traction in the UK and elsewhere, though evidence for their effectiveness remains unclear. We sought to synthesize the effectiveness of interventions integrating academic and health education for the prevention of substance use. Methods: We searched 19 databases between November and December 2015, among other methods. We included randomized trials of interventions integrating academic and health education targeting school students aged 4–18 and reporting substance use outcomes. We excluded interventions for specific health‐related subpopulations (e.g., children with behavioural difficulties). Data were extracted independently in duplicate. Outcomes were synthesized by school key stage (KS) using multilevel meta‐analyses, for substance use, overall and by type. Results: We identified 7 trials reporting substance use. Interventions reduced substance use generally in years 7–9 (KS3) based on 5 evaluations ( d = −0.09, 95% CI [−0.17, −0.01], I 2 = 35%), as well as in years 10–11 (KS4) based on 3 evaluations (−0.06, [−0.09, −0.02]; I 2 = 0%). Interventions were broadly effective for reducing specific alcohol, tobacco, and drug use in both KS groups. Conclusions: Evidence quality was highly variable. Findings for years 3–6 and 12–13 could not be meta‐analysed, and we could not assess publication bias. Interventions appear to have a small but significant effect reducing substance use. Specific methods of integrating academic and health education remain poorly understood.